Proceedings of the Unhas International Conference on Social and Political Science (UICoSP 2017) 2017
DOI: 10.2991/uicosp-17.2017.12
|View full text |Cite
|
Sign up to set email alerts
|

Coral Reef Fisheries Resource Management in Taka Bonerate National Park Based on Constructionism Perspective

Abstract: Abstract-This paper is aimed at exploring the complexity of fishery resource use of Taka Bonerate coral reef zone from the past to the present when it has become a National Sea Park. The complexity of phenomena comprises dimensions of diversity and variation of technology, change and continuity, types of ideological interaction with environment, involvement of both internal and external stakeholders with various categories, kinds and multilevel control or ownership of various fishing grounds, influence of inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…However, despite these efforts, degradation of crucial marine habitats, such as coral reefs, are still rampant. For instance, the practice of destructive fishing and extraction of corals for building materials are deemed to be persistent problems in the area [83,84]. Kusumo et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, despite these efforts, degradation of crucial marine habitats, such as coral reefs, are still rampant. For instance, the practice of destructive fishing and extraction of corals for building materials are deemed to be persistent problems in the area [83,84]. Kusumo et al .…”
Section: Discussionmentioning
confidence: 99%
“…B 377: 20210487 such as coral reefs, are still rampant. For instance, the practice of destructive fishing and extraction of corals for building materials are deemed to be persistent problems in the area [83,84]. Kusumo et al [85] estimated that in Selayar's coastal waters, damaged reef areas increase by the rate of approximately 10-50 m 2 d −1 owing to cyanide fishing.…”
Section: (C) Taka Bonerate Kepulauan Selayar Biosphere Reserve Indonesiamentioning
confidence: 99%
“…However, participants also commented that destructive fishing is (relatively) lucrative and there is weak enforcement of laws against it, making it attractive to remain in the fisheries. In TBKS there are many reinforcing factors that sustain and make destructive fishing profitable, including high-value export markets and collusion amongst networks of fishers, traders, police, and suppliers of destructive materials that encourage fishers to maintain and expand operations [22]. Past empirical studies have also observed that even if they possess the necessary skills to transition, traditional communities are often unwilling to change their livelihood strategies [46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…The fisheries, mostly small-scale fishing and trading, are the principal economic activity, but tourism is becoming increasingly important. Destructive fishing, including blast and cyanide fishing, have damaged critical habitats such as coral reefs [22]. The development of tourism within the small islands of TBKS has been a recent focus of the government, in addition to a series of donorsupported conservation and development programs, in part as a means of providing alternative livelihoods to destructive fishing and to reduce pressure on marine ecosystems.…”
Section: Study Sitementioning
confidence: 99%
“…Both islands are part of the Taka Bonerate Kepulauan Selayar Biosphere Reserve, an area where the economy and daily life of the local communities depend on natural and marine resources, such as fish inhabiting coral reef ecosystems. Despite this, the islands' coral reefs ecosystem is pressured by several anthropogenic activities, for example, destructive fishing practices and extraction of corals for building materials that are still recurrent due to their short-term economic benefits (Lampe 2017;Praptiwi et al 2021). In addition, some traditional fishing practices and anchoring of boats have been commented to contribute to the degradation of corals in the region (Moore et al 2017).…”
Section: Introductionmentioning
confidence: 99%